Death and consciousness––an overview of the mental and cognitive experience of death. (November 2014) - Parnia, Sam
Abstract : Advances in resuscitation science have indicated that, contrary to perception, death by cardiorespiratory criteria can no longer be considered a specific moment but rather a potentially reversible process that occurs after any severe illness or accident causes the heart, lungs, and brain to stop functioning. The resultant loss of vital signs of life (and life processes) is used to declare a specific time of death by physicians globally. When medical attempts are made to reverse this process, it is commonly referred to as cardiac arrest; however, when these attempts do not succeed or when attempts are not made, it is called death by cardiorespiratory criteria. Thus, biologically speaking, cardiac arrest and death by cardiorespiratory criteria are synonymous. While resuscitation science has provided novel opportunities to reverse death by cardiorespiratory criteria and treat the potentially devastating consequences of the resultant postresuscitation syndrome, it has also inadvertently provided intriguing insights into the likely mental and cognitive experience of death. Recollections reported by millions of people in relation to death, so‐called out‐of‐body experiences (OBEs) or near‐death experiences (NDEs), are often‐discussed phenomena that are frequently considered hallucinatory or illusory in nature; however, objective studies on these experiences are limited. To date, many consistent themes corresponding to the likely experience of death have emerged, and studies have indicated that the scientifically imprecise terms of NDE and OBE may not be sufficient to describe the actual experience of death. While much remains to be discovered, the recalled experience surrounding death merits a genuine scientific investigation without prejudice.